Endoscopic full-thickness resection and its treatment alternatives in difficult-to-treat lesions of the lower gastrointestinal tract: a cost-effectiveness analysis. Issue 1 (18th August 2020) - Kuellmer, Armin; Behn, Juliane; Beyna, Torsten; Schumacher, Brigitte; Meining, Alexander; Messmann, Helmut; Neuhaus, Horst; Albers, David; Birk, Michael; Probst, Andreas; Faehndrich, Martin; Frieling, Thomas; et al.
Abstract : Objective: Endoscopic full-thickness resection (EFTR) has shown efficacy and safety in the colorectum. The aim of this analysis was to investigate whether EFTR is cost-effective in comparison with surgical and endoscopic treatment alternatives. Design: Real data from the study cohort of the prospective, single-arm WALL RESECT study were used. A simulated comparison arm was created based on a survey that included suggested treatment alternatives to EFTR of the respective lesions. Treatment costs and reimbursement were calculated in euro according to the coding rules of 2017 and 2019 (EFTR). R0 resection rate was used as a measure of effectiveness. To assess cost-effectiveness, the average cost-effectiveness ratio (ACER) and the incremental cost-effectiveness ratio (ICER) were determined. Calculations were made both from the perspective of the care provider as well as of the payer. Results: The cost per case was €2852.20 for the EFTR group, €1712 for the standard endoscopic resection (SER) group, €8895 for the surgical resection group and €5828 for the pooled alternative treatment to EFTR. From the perspective of the care provider, the ACER (mean cost per R0 resection) was €3708.98 for EFTR, €3115.10 for SER, €8924.05 for surgical treatment and €7169.30 for all pooled and weighted alternatives to EFTR. The ICER (additional cost per R0 resection compared with EFTR) was €5196.47 for SER, €26 533.13 for surgical resection and €67 768.62 for the pooled rate of alternatives. Results from the perspective of the payer were similar. Conclusion: EFTR is cost-effective in comparison with surgical and endoscopic treatment alternatives in the colorectum.